Unlocking the profit potentials of an innovation: a case study of IITA hybrid plantains and bananas - Faturoti, B.; Emah, G.; Isife, B.; Tenkouano, A.; Adeniji, T.A.; Lemchi, J. (2007)
Plantain and banana hybrid varieties that are resistant to black Sigatoka disease .(a leave disease reported to have caused between 30-50% yield loss in plantain across the wortd) were disseminated by IITA plantain improvement programme in three southern states of Nigeria. This study was designed to determine the profit potentials of these disseminated technologies. Ninety farmers from fifteen villages spread across the three states were sampled and percentages applied for data analysis. It was revealed that the main disseminated technology (plantain. hybrid) was fairly adopted in the three states: Bayelsa 46%, Akwa-lbom 38% and Rivers 36%. The hybrids were disseminated in a package that was established to have influenced high adaption rates in the components that had high profit values. Such components. include sucker production in Which 45% of the respondents recorded more economic returns (money) than even fruit sales, post harvest utilization was also revealed as a main source of income in the disseminated technology as potential waste from wind damage and over ripening were turned into products such as flour (Which 93% of the respondents have adopted) and fruit juice ,respectively. The respondents as a result of the technology recorded a high profit margin of N37, 063 extra intome per t,pctare. The regression analysis· revealed that only two variables, plantain and banana constraints identification and number of innovation adopted had preductive values for the IITA hybrids adoptien (R= 0.87). It was concluded that agricultural technology dissemination should be approached in a total way with motivational factors to cater for glut that may result from massive production, "adoption and yield increases as well as ways to ensure steady and continuous innovationspread through organized seedplanting material production.